Expressed Breast Milk Contamination in Neonatal Intensive Care Unit - Gad S; Sheta MM; Al-khalafawi AI; Abu El-Fadl HA; Anany M; Sahmoud S; Amin MK (Dove Medical Press, 2021)
Suzan Gad,1 Mohamed M Sheta,2 Abeer I Al-khalafawi,3 Heba A Abu El-Fadl,1 Maha Anany,1 Shaimaa Sahmoud,1 Mona Karem Amin1 1Pediatrics and Neonatology Department, Suez Canal University Faculty of Medicine, Ismailia, Egypt; 2Pediatrics and Neonatology Department, Mansoura General Hospital, Mansoura, Egypt; 3Neonatology Department, Saqr Hospital, MOH, Ras Alkheima, United Arab EmiratesCorrespondence: Mohamed M ShetaPediatrics and Neonatology Department, Mansoura General Hospital, Mansoura, EgyptTel +971-559-865-166Email sheta99999@yahoo.comBackground: The health benefits of breastfeeding are well known. However, some ill babies including those admitted to the neonatal intensive care unit (NICU) cannot be directly breastfed. In this situation, expressed breast milk (EBM) can be used. However, breast milk is not always sterile and may be contaminated by many microorganisms. EBM contamination is probably attributed to improper technical and hygienic factors and may pose significant threats to the newborn baby. The present study aimed to document the prevalence of EBM contamination in NICU and to uncover the relevant risk factors.Subjects and Methods: The study included 118 mothers who could express breast milk for their own neonates admitted to the NICU. A checklist was used to document the steps the mothers followed during expression of milk and all steps of handling until the EBM reached the NICU. A 1 mL sample of EBM was obtained and sent to the microbiology laboratory within 20 minutes. Data obtained from the present study are expressed as number and percentage or mean ± standard deviation (SD). Statistical calculations were computed using SPSS 25.Results: In the present study, 106 (89.8%) out of the assessed 118 EBM samples were contaminated. Hygienic factors related to EBM contamination included hand only wash, possible recontamination of hands during turning taps off, lack of using cotton pads or cloth piece on nipple and breast cleaning by water only. Other factors related to EBM contamination included container cleaning by water only, fresh milk refrigeration after > 4 hours, adding freshly expressed warm breast milk to refrigerated milk expressed earlier in the same day, milk transport in plastic bags with ice packs and longer transportation time. In the contaminated samples, the most commonly isolated organisms included Staphylococcus aureus (55.7%),Staphylococcus epidermidis (21.7%) and Enterobacter (11.6%).Conclusion: The present study identified bacterial contamination in about 90% of EBM samples delivered to NICU infants. Factors related to EBM contamination include hygienic, storage and transport factors.Keywords: breastfeeding, expressed breast milk, NICU